The impact of dietary preference on household food waste: evidence from China - Zhang, Li; Ye, Linxiang; Qian, Long; Zuo, Xiuping (Frontiers in Nutrition, 2024)
Food waste jeopardizes food security and causes economic and resource losses. Household food waste is the most significant source of global food waste and urgently needs to be reduced. Based on the China Health and Nutrition Survey (CHNS), our study estimates the daily food waste data of 6,418 sample observations across China and the dietary preference scores of their household heads. Using a count regression model, our study explores the relationship between dietary preference and household food waste in Chinese households, and further explores the moderating function of household refrigerator use. The study has found that: (1) improving dietary preference score can significantly reduce household food waste ratio, and robustness tests support this finding. (2) There is a positive moderating effect of refrigerator use in the process of how dietary preference influence food waste. (3) Heterogeneity analysis shows that the impact of dietary preference on household food waste varies by gender and age of the household head, household size, economic level, urban-rural type, and north-south region. Our study provides evidence that improving dietary preference can reduce household food waste in China, which has certain implications for waste reduction in other developing countries.